The Diagnosis and Context of a Facial Deformity from an Anglo‐Saxon Cemetery at Spofforth, North Yorkshire. (15th September 2011) - Craig, E.; Craig, G.
ABSTRACT An individual aged between 6 and 7 years at death from a 7th to 9th century cemetery at Village Farm, Spofforth, North Yorkshire, presented significant pathological swelling to the left facial bones. The ectocranial surface was bulbous and uneven, and the expanded diploë was densely packed with a mass of thick trabeculae. Radiographic and histological analysis, in combination with the macroscopically observed pathological changes, supported the differential diagnosis of fibrous dysplasia. The skeletal changes to the left face and jaw would have resulted in a significant facial deformity. Examples of individuals with physical impairments or disfigurements from Anglo‐Saxon cemeteries are rare. Nevertheless, it seems that a significant proportion are afforded unusual burial practices more often associated with deviancy, for example, at the edge of cemeteries or on a reversed orientation, seemingly indicating that their diminished physical capabilities or altered physical appearance had a detrimental effect on their social status. The child from Spofforth was, however, buried in a normative manner, extended, supine and in a plain earth‐cut grave, with no indication that their facial deformity had prompted unusual funerary provision. This example of facial disfigurement contributes to a growing corpus of potentially disabled individuals from early medieval England. Copyright © 2011 John Wiley & Sons, Ltd.